1998
DOI: 10.12968/bjom.1998.6.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Special care or segregation?

Abstract: This paper will focus on the identified need for a specialised maternity service for drug-using women in the inner-city area of Manchester and argue that a collaborative initiative was vital if a comprehensive specialist service was to be provided for the increasing number of pregnant drug-using women. The importance of an ongoing harm-reduction education programme for service providers is also emphasised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This led us to question neonatal management generally, as few data are available regarding the appropriate treatment of infants exposed to multiple drugs. We suggested changes in hospital policy (Macrory & Crosby 1995; Macrory 2001; Frayne & Macrory 2001; Macrory & Harbin 2001) so that infants would benefit from a different approach to the resolution of withdrawal symptoms such that they did not always require pharmacological intervention, included swaddling to decrease sensory stimulation and allowing uninterrupted rest periods, or offering frequent small feeds.…”
Section: Discussionmentioning
confidence: 99%
“…This led us to question neonatal management generally, as few data are available regarding the appropriate treatment of infants exposed to multiple drugs. We suggested changes in hospital policy (Macrory & Crosby 1995; Macrory 2001; Frayne & Macrory 2001; Macrory & Harbin 2001) so that infants would benefit from a different approach to the resolution of withdrawal symptoms such that they did not always require pharmacological intervention, included swaddling to decrease sensory stimulation and allowing uninterrupted rest periods, or offering frequent small feeds.…”
Section: Discussionmentioning
confidence: 99%
“…Within this overall strategy, the approach to service delivery for substance‐using women differs between areas and a number of models have been established. Options include incorporating drug dependence staff within antenatal clinics (London and Caldwell, 1990), the drug liaison midwife (Macrory, 1998), specialist maternity services (Hepburn, 1997) and systems of normalization where substance‐using women are largely incorporated within the mainstream service (Siney, 1999). The principles of shared care are the basis for all of the established models, but there are both advantages and disadvantages to each strategy (Klee et al.…”
Section: Introductionmentioning
confidence: 99%
“…Within and between professional groups, it is suggested that the best care is achieved through development and implementation of a protocol to address the specific needs of substance‐using women (Hepburn, 1993; Siney, 1995; Macrory, 1998; Advisory Council on the Misuse of Drugs, 2003; Scottish Executive, 2003). However, in a recent Scottish survey, around only half of maternity units reported having specific antenatal protocols for the management of substance misuse (Advisory Council on the Misuse of Drugs, 2003).…”
Section: Introductionmentioning
confidence: 99%